THE EFFECT OF DIABETES ON THE CARDIOVASCULAR SYSTEM - Yunusova Guzal Fayzullayevna (World Scientific Research Journal, 2025)
Abstract: This article studies the impact of type 2 diabetes mellitus (T2DM) on the cardiovascular system. The study analyzed the incidence of ischemic heart disease, hypertension, atherosclerosis, and stroke among diabetic patients. It also identified the mechanisms by which diabetes affects the activity of the heart muscle and the function of the circulatory system. The article also provides recommendations for early detection and prevention of cardiovascular complications based on statistical data.